THE RELATIONSHIP BETWEEN HUSBAND'S SOCIAL SUPPORT AND BREASTFEEDING SELF-EFFICACY IN PRIMIPARA MOTHERS - Dinda Fitri Annisa; Tesi Hermaleni (Ravine Publisher, 2023)
The correlation between husband's social support and breastfeeding self-efficacy in primiparous mothers. This study aims to see the relationship between social support, especially from the husband, and the mother's self-confidence in breastfeeding. Respondents in this study were 40 primiparous mothers with children aged 0-6 months living in Tanah Datar Regency—data collection using a purposive sampling technique. The husband's social support scale is designed based on the theory proposed by Sarafino (2004) as the independent variable (X), and the breastfeeding self-efficacy scale uses the Breastfeeding Self Efficacy Scale - Short Form (BSES-SF) scale as the dependent variable (Y). The results of data analysis using product moment found that (p = .000) < .005, meaning that there was a significant positive relationship between the husband's social support and breastfeeding self-efficacy in primiparous mothers.